Regional governance in the new CEE member states of the EU - Daniel Pop (Competitio, 2008)
This paper discusses how the CEE-10 countries complied with the EU conditionality in the field of regional policy, examining whether the territorial reforms implemented were carried out leading to the enrooting of sub-national regional governance structures. Following the discussion of the EU requirements in the field of regional policy, I turn to a case by case analysis of how the meso-level government tiers were set up in the CEE-10 countries. The analysis leads to the finding that the limited interest in the CEE-10 countries to develop extensive regional governance structures by creating new autonomous sub-national governance structures coupled with the frequent contradictory and often unofficial requirements by the European Commission during negotiations, has led to a weak institutionalization of meso-level governments when compared to the institutional and policy structures within the EU-15.